"The Diary of Frida Kahlo": The genre, the book, the work. - Loizou, Melissa. (University of Ottawa (Canada), 2002)
This study explores some fundamental aspects of The Diary of Frida Kahlo, namely its classification as a diary, the impact of the prologues of the different versions on the diary's reception, and the various dialogues taking place within it and the rest of Kahlo's artistic production. The first part focuses on the classification of this work as a diary. The theoretical sources utilized to establish the characteristics of the diary genre are: Le journal intime by Beatrice Didier, and the scholarly article by Valerie Raoul, "Women and Diaries: Gender and Genre". This chapter demonstrates that there are certain aspects of Kahlo's diary that indeed correspond to the genre whereas other elements distance it from this classification. In the second part of this study, the role and impact of the introduction and prefatory essays is examined. The basis of the analysis of the different prefaces is Gerard Genette's concept of the paratexte as elaborated in his book, Seuils. In the final part of the study an interpretation of Kahlo's diary is offered which focuses particularly on the notion of dialogue. (Abstract shortened by UMI.)
Keywords: Biography.